2 D Manganese Vanadate Nanoflakes as High‐Performance Anode for Lithium‐Ion Batteries. Issue 5 (5th March 2014) - Deng, Dingrong; Zhang, Yanjun; Li, Gen; Wang, Xueyun; Gan, Li‐Hua; Jiang, Li; Wang, Chun‐Ru
Abstract Nanometer‐sized flakes of MnV2O6 were synthesized by a hydrothermal method. No surfactant, expensive metal salt, or alkali reagent was used. These MnV2O6 nanoflakes present a high discharge capacity of 768 mA h g−1 at 200 mA g−1, good rate capacity, and excellent cycling stability. Further investigation demonstrates that the nanoflake structure and the specific crystal structure make the prepared MnV2O6 a suitable material for lithium‐ion batteries.